Exploring clinician expectations and preferences of library subject guides. - Biszaha, Anna (Medical Reference Services Quarterly)
Using semi-structured interviews, this study aimed to qualitatively explore the expectations and preferences of clinical users when engaging with library subject guides. Participants were generally unaware that subject guides existed but showed some preference toward guides that were quick and easy to use and provided independent learning materials, as well as resource access and guidance. Barriers to use in clinical practice included time, awareness, and issues of guide design and cognitive load. The results of this study will help inform the development of customized subject guides targeting this special population.